Cystic Leukoencephalopathy with Normocephaly - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2005)
A new syndrome of nonprogressive encephalopathy with normo- or microcephaly and early onset of psychomotor impairment is described in 15 children, in a report from the University of Gottingen and other centers in Europe and the US.